Penggunaan Metode Bioassay untuk Mendeteksi Pergerakan Herbisida Pratumbuh Ametrin dan Diuron dalam Tanah - Nanik Sriyani; Abdul Kadir Salam (Fakultas Pertanian, Universitas Syiah Kuala, 2008)
The Use of Bioassay to Detect the Movement of Ametryne and Diuron Herbicides in the SoilABSTRACT. This study is the third step from a series of studies aim to develop method to detect the present and quantity of herbicides in soil and water through a simple, easy, cheap, but accurate bioassay technique. Bioassay is a method which measure response of living organism to determine the presence or quantity of substances in a sample on medium, such as soil, water, and other materials. In this study, bioassay developed in the earlier studies was used to detect movement of ametryne and diuron herbicides in soil. Study was carried out using soil column method. Treatment were arranged factorially in a completely randomized block design with 3 replicates. Two ultisol soil types: Podsolik Merah Kuning (PMK) and Latosol cokelat (LC), and 2 preemergence herbicides: ametryne and diuron were tested. To calculate the amoung of herbicide using bioassay, each standard curve for ametryne and diuron (relationship between the growth of indicator plant as a respon of the amount of herbicide) were developed. Using these standard curves, the amount of ametryne and diuron was calculated based on the growth rate of indicator plant. Result showed that bioassay method can be utilized to detect herbicide movement in soil. The amount and the rate of herbicides movement was determined by soil and herbicide types. In PMK, ametryne was detect at the all soil dept from 1 through 4 week after application (WAA), however at 8 WAA this herbicides was only detected in 20-40 cm soil depth in limited amount, while at 12 WAA there was no ametryne detected in all soil depth. In LC, ametryne was also detected at all soil depth 1 day after application (DAA) through 1 WAA, while at 2 through 4 WAA ametryne was detected at 0-30 cm soil depth. At 8 and 12 WAA there was no more ametryn detected in all soil depth. The movement of diuron herbicide was more restricted compared to ametryn, both in PMK or LC. In PMK, from DAA 1 through 4 WAA diuron was only detected at 0-20 cm soil depth. At 8 WAA this herbicide was found at 10-20 cm soil depth, while at 12 WAA there was no diuron detected in all soil depth. In LC, most of diuron applied was still present in the upper soil colom (0-10 cm), while at 10-20 cm soil depth this herbicide was present in the limited amount 1 DAA through 1 WAA, diuron was detected only at 0-10 cm soil depth, meanwhile from 4 through 12 WAA there was no diuron detected at all soil depth.